Influence of biological control agents Helicoverpa armigera nuclear polyhedrosis virus (HaNPV) on mortality twig caterpillar (Ectropis bhurmitra Wlk.) - Joko Santoso; Merry Antralina (Jurnal Penelitian Teh dan Kina, 2011)
The objective of this research was evaluate effectiveness of Helicoverpa armigera Nuclear Virus Polyhedrosis virus (HaNPV) on twig caterpillar (Ectropis bhurmitra Wlk) mortality. The experiment was conducted at the Research Institute for Tea and Cinchona, Gambung, Bandung, elevation of + 1.300 m asl, from March 2011 till June of 2011. A completely randomized design was used with 12 treatments and replicated twice. Aplication of four level concentrations of HaNPV on three stadia of the twig caterpillar larvae were performed. The HaNPV concentrations were 4 x 106 PIB/mI, 4 x 104 PIB/ml, 4 x 102 PIB/ml and 0 PIB/ml, and stadia of the twig caterpillar larvae were 2, 3, and 4. The results indicated that direct application of HaNPV on twig caterpillar larvae had similar effect in mortality of the larvae, either in the laboratorium or in the greenhouse, with level of mortality was 70% within four to ten days periode. Laboratory expeÂrimentation indicated that 4 x 102 PIB/ml concentration of HaNPV applied directly on stadia 3 and 4 was effective in suppressing Ectropis bhurmitra Wlk. larva population while for larvae stadium 2 the effective concentration was 4 x 104 PIB/ml. In greenhouse experiment revealed that 4 x 102 PIB/ml concentration of HaNPV was effective in suppressing larvae of stadium 2 and stadium 4, while until the end of the experiment no indication of maksimum mortality in stadium 3 population.